Optimalisasi PCR-RAPD dan Identifikasi Morfologi Tanaman Kumis Kucing di Provinsi Bengkulu - Marulak, Simarmata; Inoriah, Entang; Haquarsum, Eka Jan Virgin (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2014)
A research was conducted with objectives to look for the best DNA extraction methods for whisker plants, to optimize random amplified polymorphism DNA-polymerase chain reaction (RAPD-PCR) by testing annealing temperatures and screening random primers, and to identify morphology of these plants in Bengkulu Province. DNA’s extraction followed the protocols of Geneaid and Epicentre kits were conducted for 11 clones of whisker plants. Optimalization of RAPD-PCR was tested by six levels of annealing temperatures and 16 random primers. Morphological identifications were done in 4 locations in Bengkulu Province, i.e. Bengkulu City, Kuro Tidur (North Bengkulu), Kepahiang, dan Air Dingin (Curup) Results showed that Geneaid demostrated better results as compared with Epicentre. RAPD-PCR performed optimum at 34.8 oC of annealing temperature; whereas, three random primers showed optimal amplification were I-01, N-01 and P-01, which nucleotide sequences were ACCTGGACAC, CTCACGTTGG, and GTAGCACTCC, respectively. Meanhile, no morphological variatons was found among the the samples, except that growths of whisker plants were taller and bigger in Kepahyang and Air Dingin Curup than in others.